Challenges of Safety Women Work-life Balance in Construction Site Risk - Abdullah, Nur Ain Najwa; Abd Rahim, Mohd Hilmi Izwan (Journal of Techno-Social, 2025)
Now a day, must women in professionals in a variety of disciplines. However, striking a balance is challenging, especially given one's professional and domestic obligations. Women workers are few in the construction business because of the many obstacles they face, including the industry's preponderance of men. Because of these barriers, women are less likely to work on construction sites. The focus of this research is on the experiences of women in the construction industry. The objectives of this research are to identify the challenges of women in construction site work-life. Second, to identify the current practice of women in construction industry and to suggest the well-being working conditions for women in construction site. Therefore, this research was done to identify barriers and propose solutions for the safety and well-being of women in the construction industry. This research utilises a literature review alongside quantitative techniques which surveying G7 contractors. The area in Johor Bahru where this research was done is now under construction. Out of a total of 719 contractors, 248 (or 36%) were randomly chosen to participate in this survey. The SPSS statistical package was used to analyse the results of the questionnaire distribution study. The finding shows difficulties women face on construction sites, as well as recommendations for improving their working circumstances, require a descriptive statistical study, including frequency distribution and mean score. Additionally, the construction sector is required to make it easier for women to advance their careers in the field, particularly on building sites, by providing them with the self-assurance, opportunity, and space to do so. In conclusion, the findings of this research have implications for increasing the number of professional women in the construction business.